THE EXHAUST GAS EMISSION TEST ON HONDA BRIO SATYA WITH VARIATION OF FUEL AND ROTATION ENGINE - Mujahid Wahyu; Hadi Rahmad (VANOS Journal of Mechanical Engineering Education, 2018)
The purpose of this research are: 1) Knowing the exhaust gas emission test result from Honda Brio Satya with variation of fuel 2) Knowing the type of fuel that produces the lowest exhaust gas emission value. This research is using experimental method. This research was conducted in the automotive workshop of SMKN Udanawu Blitar Regency. Test media is a Honda Brio Satya type E 2017. The emission test used QROTEC QRO 402 gas analyzer. The results show that: 1) There is influence of fuel type to vehicle exhaust emissions, both at idle and intermediate rotation; 2) The average of CO gas emissions at idle rotation with fuel of each premium, pertalite and pertamax are 0.026%, 0.023% and 0.003%. The average of HC gas emission at idle rotation in each fuel type are 87 ppm, 86.3 ppm and 30 ppm. Thus, pertamax fuel produces the lowest level of exhaust emissions. The third fuel type still meets the threshold of motor vehicle emissions threshold in accordance with PERMEN LH No. 5 of 2010 so it is worthy to be used as an environmentally friendly learning media.